The Comparison Between The Satun Dialect and The Patani Dialect of The Melayu Language - Menjamin, Sumaiyah; Chema, Andareena (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study aims to describe the comparison of the Satun dialect and the Patani dialect of the Malayu language. Satun is a province located to the west of Peninsular Malaysia, while Patani is located in the eastern part of Malaysia, namely in Kelantan. This research is a descriptive field research about BMDS and BMDP dialect forms. The data collected are forms of dialect used by people who use BMDS and BMDP. The Data was collected via interview, the matching method, and by analyzing the basic vocabulary comparison method based on 200 Swadesh words. Data obtained from 2 sources, BMDS-informant and DMDP-informant. The results of this study are a form of comparison between the Satun dialect and the Patani dialect of the Malayu langauge. (1) There are 48 vocabularies with the same form and (2) 152 vocabularies with different forms. Both dialeks are based in the same language, Austronesian Malay. Based on the location of different provinces, the location gets influence from the loghat of the area bordering Kedah and Kelatan. Therefore, these two languages have a regional language or dialect that is together and different in the form of words and sounds.